(untitled) (Nexo Revista Científica, 2021)
Carbon nano tubes (CNTS) have two basic structure as single-walled and multi-walled based on hexagonal plexus of carbon atoms. CNTs can serve as platforms to conjugate other compounds specially in medications purposes by immobilization of biomolecules at their surface. Dopamine and serotonin are two biological molecules which have bifunctional activities as hormone and neurotransmitter. These two molecules have important roles as neurotransmitters in the central and peripheral nervous systems but serotonin functions as a mood regulator, while dopamine is connected to the “pleasure center”. In this article we optimized molecular and structural properties of connected dopamine and serotonin with SWNTS with four different diameters (7.0,7.5,7.7 and 10.0 nm) by using molecular quantum methods such as NMR shielding tensor data by B3LYP level of theory with 6-31 G(d) as a basis set, mk and frequency methods. Theoretical computations were performed to study NMR chemical shift data including magnetic shielding tensor (σ, ppm), shielding asymmetry (η), magnetic shielding anisotropy (σaniso), magnetic shielding isotropy (σiso) , skew of a tensor (Κ) and chemical shift anisotropy (Δσ) and span (Ω) at various rotation angles around a specific rotation , physical and chemical properties of atomic nuclei , frequency data by B3LYP/6-31g level of theory and POP method using gaussian 09 program.